(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This study examines the effect of different planting dates on the growth, development, and yield of the “Qizil toj” and “Salfer” kohlrabi cabbage varieties. The results showed that planting dates significantly affected the growth and yield formation of kohlrabi cabbage. The highest yields were observed in the “Salfer” variety at 18.6 t/ha and the “Qizil toj” variety at 16.7 t/ha. The findings of this research make it possible to determine the optimal planting dates for achieving a high yield from kohlrabi cabbage.